2021
DOI: 10.1007/s11255-021-02809-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostatic apex shape (Lee types) and urethral sphincter length in preoperative MRI on very early continence rates after radical prostatectomy

Abstract: Purpose To test the effect of anatomic variants of the prostatic apex overlapping the membranous urethra (Lee type classification), as well as median urethral sphincter length (USL) in preoperative multiparametric magnetic resonance imaging (mpMRI) on the very early continence in open (ORP) and robotic-assisted radical prostatectomy (RARP) patients. Methods In 128 consecutive patients (01/2018–12/2019), USL and the prostatic apex classified according to Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Indeed, Lee et al [60] proposed a new classification of prostatic apex shape on MR images: type A defined as a prostatic apex overlapping the membranous urethra both anteriorly The last group proved to be linked to an higher rate of early return to urinary continence. Furthermore, a more recent experience too proved how type C and D were associated to very early continence restoration after catheter removal following RP [61]. Moreover, the prostate apex can be close to the skeletal fibers of the urogenital diaphragm, and therefore apical lesions should be precisely described because they might involve these structures.…”
Section: Prostate Apex Descriptionmentioning
confidence: 99%
“…Indeed, Lee et al [60] proposed a new classification of prostatic apex shape on MR images: type A defined as a prostatic apex overlapping the membranous urethra both anteriorly The last group proved to be linked to an higher rate of early return to urinary continence. Furthermore, a more recent experience too proved how type C and D were associated to very early continence restoration after catheter removal following RP [61]. Moreover, the prostate apex can be close to the skeletal fibers of the urogenital diaphragm, and therefore apical lesions should be precisely described because they might involve these structures.…”
Section: Prostate Apex Descriptionmentioning
confidence: 99%
“…From a clinical point of view, current findings may be attributable to a potential malfunction of the external sphincter; either pre-existing or by an injury of the urethral sphincter during RP [18,27]. Even though full functional-length of urethral sphincter preservation was routinely performed in all patients, interindividual anatomical and tumor characteristics may have influenced the extent of preservation, and led to potential injury of the sphincter [28]. As a consequence, PAD-test results did not only profoundly correlate with early continence rate, but could also be taken as a measurement tool to estimate the severity of early incontinence after RP.…”
Section: Discussionmentioning
confidence: 94%
“…Previous anatomical and functional studies have demonstrated that a substantial functional part of the urethral sphincter is located intraprostatically between the colliculus seminalis and apex [ 10 , 23 , 24 ]. Bearing in mind that the apex shape varies widely among patients, up to 40% of the functional part of the urethral sphincter is covered by parenchymal apex tissue [ 25 27 ]. As a consequence, meticulous preservation of the full functional-length of the urethra would include preserving a substantial part of the urethral sphincter complex as well [ 10 ].…”
Section: Discussionmentioning
confidence: 99%